Draft Annual Plan 2008-2009 Part-I Government of Sikkim - Planning Commission (Planning Commission, 2008)
Sikkim is a small State in the eastern Himalaya with an area of 7096 Sq. Km. lying between 27° 04'46" and 28° 07'48" north latitude and 88° 58" and 88° 55'25" east longitude. Sikkim became the 22nd State of India on 16th May, 1975. Sikkim is one of the special category States and is also the 8th Member of the North Eastern Council. It is a unique mountainous State encircled by three different international boundaries.
Development Planning, Economic Reforms and North Eastern Council Affairs Department, Government of Sikkim